Evaluation of Solid Medical Waste Management in Public Health Center - Arifqah Dhiya Ulhaq; Inoy Trisnaini; R. Azizah R. Azizah; Seto Anjar Ramadhan (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Inadequate waste management in healthcare facilities can negatively impact healthcare workers, patients, and the environment. As a daily healthcare service unit, Talang Ratu Public Health Center is required to manage medical waste properly. This study aims to analyze the solid medical waste management process at Talang Ratu Public Health Center. This descriptive qualitative study was conducted at Talang Ratu Public Health Center, Palembang City, from from november to december in 2022 approach to explore the management practices, facilities, and infrastructure involved in handling solid medical waste. Eight informants were selected through purposive sampling, consisting of two sanitarians/health workers, one cleaning staff, and five heads of outpatient departments. Data were collected through interviews, observations, and documentation, and analyzed using triangulation techniques. Sources of medical waste include the Maternal and Child Health (MCH) unit, pharmacy, laboratory, and dental clinic. Overall, the waste management process has been implemented adequately in accordance with the Ministry of Environment and Forestry Regulation No. 6 of 2021. Waste is segregated using color-coded containers and transported after service hours by staff wearing full Personal Protective Equipment (PPE). However, transportation is still conducted manually due to the lack of dedicated trolleys. Health risks also arise because temporary waste storage last between two weeks and one month without proper temperature control. The study recommends improving transportation and storage systems to enhance the safety and efficiency of solid medical waste management.